Resection for hepatocellular carcinoma: Is it justifiable to restrict this to the American Association for the Study of the Liver/Barcelona Clinic for Liver Cancer criteria? - Chow, P.K.-H. (2014)
10.1111/j.1440-1746.2011.07034.x